God and his attributes: Lessons on Islamic Doctrine 1 - Lari, Sayyid Mujtaba Musavi (Islamic Education Center, 1989)
God and his attributes: Explains the monotheistie view of Islam in twenty-one lessons with brilliant clarity. Drawing heavily on the Traditions of the prophet as well as extensive quotes from the Quran, the author convincingly refutes the materialist point of view while presenting sound reasouning for the monotheistic world view.